"Mizrahi religion is for laymen custom": Construction of an ethnoreligious hierarchy in boarding yeshiva high schools in Israel in the 1980s. Issue 2 (3rd July 2021) - Trabelsi, Erez
ABSTRACT: Underpinned by Bourdieuian theory, specifically, Bourdieu's argument in Distinction (1984), this study investigates the instituting of an ethnoreligious social order in yeshiva high schools in Israel in the 1980s, as expressed in the personal accounts of Mizrahi graduates of these schools. The research findings indicate that the educational staff of the yeshiva high schools, being mostly Ashkenazi, constructed Ashkenazi religion as standard, and Mizrahi religion as flawed and out of place in the religious life of the yeshiva high school. The religious and liturgical practices in the yeshiva high schools followed purely Ashkenazi traditions, while the educational staff insisted on marking the inferiority of Mizrahi religion by means of various remarks regarding the students' ethnic identity, in addition to inversion rituals that degraded Mizrahi religious traditions. The study findings correspond with Religious Zionist society's preoccupation with the preference of the Ashkenazi version of religion to the Mizrahi version in state religious education in general, and in yeshiva high schools in particular.